O Estado, a política liberal e a biopolítica - França, Sonia Aparecida Moreira [UNESP]; Zanetti, Fernando Luiz [UNESP] (Universidade Federal Fluminense, Departamento de Psicologia, 2014)
This essay discusses some liberal political actions and their relations with the state. Considering some of their propositions, we ask: what power relations does that social practice respond to? Under what circumstances is the liberal politics interested in the government of men? From a study of the practices called corporate philanthropy we can indicate some strategies and tactics of such politics. Among which: the construction of the modern state, the development of various techniques of social control and the focus changes regarding the analysis of capitalism productive forces that intervene within the economic normality curves inherent in the population phenomena.

Nesse ensaio, problematizamos ações da política liberal e suas relações com o Estado. Ao considerar algumas de suas proposições, questionamos a quaisrelações de poder essa prática social responde. Em que circunstâncias ela se interessa pelo governo dos homens? A partir do estudo das práticas intituladas como filantropia empresarial podemos indicar algumas estratégias e táticas dessa política. Entre as quais destacamos: a construção do Estado Moderno, a elaboração das diversas técnicas de controle social e as mudanças de foco com relação às análises das forças produtivas do capitalismo, que passaram a intervir nas curvas de normalidade econômica imanentes aos fenômenos da população.
The state, liberal politics and biopolitics
Keywords: liberal politics; strategies of social control; Michel Foucault; política liberal; estratégias de controle social; Michel Foucault